2014
DOI: 10.4155/bio.14.310
|View full text |Cite
|
Sign up to set email alerts
|

A Device for Dried Blood Microsampling in Quantitative Bioanalysis: Overcoming The Issues Associated Blood Hematocrit

Abstract: The novel volumetric absorptive microsampling device has the potential to deliver the advantages of dried blood spot sampling while overcoming some of the issues associated with the technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(117 citation statements)
references
References 26 publications
6
110
0
1
Order By: Relevance
“…The Hct effect in DBS is mainly due to a constant punch size in spite of variable size of blood spot depending on the Hct, however, impacts of Hct on DBS might be partly overcome by optimization in extraction procedure as observed in the present study. Mitra has overcome the Hct-dependent variable volume of blood subjected to the assay as demonstrated by Spooner et al [3]. The present study has successfully demonstrated that optimization in extraction process to give high and consistent extraction recovery is of importance for accurate assay using Mitra.…”
Section: Impacts Of Hematocrit On Accuracysupporting
confidence: 63%
See 1 more Smart Citation
“…The Hct effect in DBS is mainly due to a constant punch size in spite of variable size of blood spot depending on the Hct, however, impacts of Hct on DBS might be partly overcome by optimization in extraction procedure as observed in the present study. Mitra has overcome the Hct-dependent variable volume of blood subjected to the assay as demonstrated by Spooner et al [3]. The present study has successfully demonstrated that optimization in extraction process to give high and consistent extraction recovery is of importance for accurate assay using Mitra.…”
Section: Impacts Of Hematocrit On Accuracysupporting
confidence: 63%
“…In addition, some abuses during sampling and handling were also evaluated such as repeat dipping of the tip in samples, effects of submerging of the tip and postsampling abuses including tip touched against paper towel. In addition, the latest paper by Spooner et al [3] has demonstrated that the device absorbed a fixed volume of whole blood (~10 μl) regardless of Hct values across six different laboratories, suggesting minimal interlaboratory differences in sampling volume via Mitra. However, to the best of our knowledge, impacts of Hct on the accuracy of analyses have not been reported except in one recently pub-lished paper [4].…”
mentioning
confidence: 96%
“…46,47 Furthermore, the collected sample volume is independent of the hematocrit level. 48 It has been very recently demonstrated that, when aiming at multi-elemental analysis, this methodology allows the recovery of the sample in a simple way by applying a single extraction step with 1% HNO 3 without any further manipulation.…”
Section: Analysis Of Real Samplesmentioning
confidence: 99%
“…Thus, where estimation of HCT is made, there may be a need to enforce strict acceptance criteria for quality of received DBS specimens, such as a minimum apparent volume [5]. Last, it is worth noting that advanced collection techniques involving volumetric application of blood to filter paper for whole-spot analysis could obviate any need to estimate sample hematocrit from DBS [14,15].…”
Section: Discussionmentioning
confidence: 98%